Cannabis and Sleep: A Systematic Review of the Effects of Cannabinoids on Sleep Disorders - Luchowska, Anna; Sroczyńska, Monika; Żaczek, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction: Sleep disorders are a common problem in society in the modern world. Patients are increasingly seeking alternative treatments for insomnia in order to reduce the side effects of prescription drugs. A new trend is the use of cannabinoids contained in cannabis plants to treat sleep disorders, making patients looking for a solution to their problem more and more eager. Aim of the study: The purpose of this paper is to present contemporary knowledge of the therapeutic benefits of cannabis compounds in treating sleep disorders and improving sleep parameters. Materials and methods: The National Center for Biotechnology Information/PubMed and Google Scholar medical databases were comprehensively analyzed by entering the keywords: cannabis, sleep disorders, insomnia, cannabinoids, THC, CBD in their respective configurations. Analyzing the searched literature, data from 18 scientific articles from the last five years (2017-2022) were evaluated. Results: Cannabinoids may have benefits in sleep-related disorders. The literature does not agree on the effectiveness of their use in treating sleep disorders. The highly variable availability of cannabinoid formulations on the market makes it difficult to develop appropriate dosages for the treatment of insomnia. Conclusions: Research on cannabis and sleep is in its early stages and needs to be continued in order to improve knowledge. There is a need for further long-term studies that are rigorously controlled and use larger study groups.